Outcome of Acute Burn Injuries in a Tertiary Care Centre of Kathmandu Nepal - Devkota, Manish; Sharma, Samit; Rayamajhi, Sangam; Shrestha, Jayan M; Lohani, Ishwar (Journal of Institute of Medicine Nepal, 2020)
Introduction Burn injuries are associated with higher morbidity and mortality especially in middle and low-income countries. The objective of the study is to assess the outcome of acute burn injuries in a tertiary care center of Kathmandu, Nepal.MethodsThis is a descriptive cross-sectional study of the clinical data of acute burn patients admitted from January 2016-December 2018.ResultsOut of 124 patients with burn injuries, there were more females (n=65, 52.4 %) than males (n=59, 47.6%). Flame burn was the most common mode of injury (n=71,57.3 %) followed by scald (n=22,17.7 %). Thirty-eight (30.6%) patients arrived to hospital on the same day of injury. The average time required to reach our hospital was 24 hours. The most frequently involved site was lower extremities (n=40, 32.26%) followed by upper extremities (n=33, 26.62%). Total body surface area (TBSA) involved in the burn injury ranges from 10% to 50% with a median of 15%. Hospital stay was 14 to 58 days with a median of 17 days. Partial thickness burn was seen in 114 (91.94%) patients whereas 10 (8.06%) patients had full thickness burn. Surgical intervention was needed in 71 (57.26%) patients. Among 71 patients, 12 patients underwent surgery twice. Fifty-two (41.94%) patients were managed conservatively. The mortality rate was 4.03%.ConclusionAdult female population is at high risk for burn injuries mostly due to flame burn. Delay in reaching care has also contributed for poor outcome of burn injuries. Majority of burn injury patients needed surgical intervention and hence improvement in surgical aspects can lead to better outcome of burn injuries.Keywords: